Update on diagnosis and management of childhood epilepsies - Sameer M. Zuberi; Joseph D. Symonds (Elsevier, 2015)
Objectives: To review the current evidence base for the diagnosis and management of the childhood epilepsies and to draw attention to the current gaps in this evidence base. The focus will be on therapeutic aspects. Current International League Against Epilepsy (ILAE) terminology will be described and used throughout the discussion. The review will draw attention to recent advances that have been made in both our understanding and treatment of the childhood epilepsies. Potential future directions for research and treatment options will be discussed. Sources: Original articles relevant to the subject were obtained from the MedLine database using pertinent MeSH terms. Relevant papers were read and assimilated. Citation searching was used. Summary of the findings: Epilepsy is a major cause of global disease burden. Childhood epilepsies are a heterogeneous group of conditions. A multi-axial diagnostic approach should be taken prior to making treatment and management decisions for any individual patient. For the majority of patients, successful control of seizures can be achieved with a single medication. However, a significant minority develops refractory disease. Epilepsy surgery can provide cure for a carefully selected group of these cases. Conclusions: There remain significant gaps the evidence base for treatment in several areas of childhood epilepsy. Concerted multi-center efforts should be made to try to close these gaps. A personalized medicine approach may help to reduce the proportion of refractory cases of childhood epilepsy in future. Resumo: Objetivos: Analisar a base de evidências atual para o diagnóstico e tratamento das epilepsias da infância e chamar a atenção para as lacunas atuais nessa base de evidências. O foco será os aspectos terapêuticos. A terminologia atual da Liga Internacional contra a Epilepsia (ILAE) será descrita e utilizada na discussão. A análise chamará a atenção para os recentes avanços em nosso entendimento e no tratamento das epilepsias da infância. Serão discutidas possíveis orientações futuras para as opções de pesquisa e tratamento. Fontes de dados: Trabalhos originais relevantes para o assunto foram obtidos da base de dados MedLine usando termos relevantes do MeSH. Os trabalhos relevantes foram lidos e assimilados. Foi usada pesquisa de citações. Resumo dos dados: A epilepsia é uma das maiores causas da carga global de doenças. As epilepsias da infância representam um grupo heterogêneo de doenças. Uma abordagem multiaxial do diagnóstico deve ser realizada antes da tomada de decisões de tratamento de qualquer paciente individual. Na maioria dos pacientes, o controle bem-sucedido das crises pode ser obtido com uma única medicação. Contudo, uma minoria significativa desenvolve doença refratária. A cirurgia de epilepsia pode curar um grupo cuidadosamente selecionado desses casos. Conclusões: Ainda existem lacunas significativas na base de evidências de tratamento em diversas áreas de epilepsia da infância. Devem ser envidados esforços multicêntricos concertados para tentar fechar essas lacunas. Uma abordagem médica personalizada pode ajudar a reduzir a proporção de casos refratários de epilepsia da infância no futuro. Keywords: Epilepsy, Epilepsies, Diagnosis, Management, Child, Palavras-chave: Epilepsia, Epilepsias, Diagnóstico, Tratamento, Infância